Isolation and detection of rabies virus in the fecal contents of naturally infected fruit bats (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
ONRAB® is a recombinant rabies vaccine used to as an oral vaccine in wildlife species such as: fox (Vulpes vulpes), raccoons (Procyon lotor), and striped skunks (Mepthis mephitis). The viral vector in the ONRAB® vaccine is human adenovirus type 5 (Had5) with the gene for rabies glycoprotein incorporated into its genome. Had5 is a relatively safe and well-studied virus, which is used in many vaccine formulations. Canadian researchers (e.g., Knowles et al. 2009) have conducted vaccine efficacy and safety studies using ONRAB® in 18 species of animals. Our research expands on the species previously evaluated. We studied the vaccine as it relates to its safety in wildlife species likely to contact the ONRAB® vaccine during oral rabies vaccine (ORV) campaigns in the United States. We investigated the effects of high doses of the ONRAB® vaccine in wood rats (Neotoma spp.), eastern cottontail rabbits (Sylvilagus floridanus), Virginia opossums (Didelphis virginiana), Eastern wild turkey (Meleagris gallopavosilvestri), and fox squirrel (Sciurus niger), whose range overlaps with ORV target species in the United States. After inoculation of the animals we performed realtime PCR on fecal swabs, oral swabs, and tissues to detect viral DNA. Our preliminary results mostly concur with the findings of Knowles et al. (2009). By 7 days postvaccination, turkeys, opossums, and cottontails had all stopped shedding viral DNA. One woodrat and five fox squirrels still had detectable levels of viral DNA in fecal swabs on 7 days post-innoculation. However, 45% of fox squirrels were co-infected with Leptospira interrogans, which may be a confounding factor to the prolonged detection of viral DNA in fecal swabs from these animals. There were no significant findings on gross histology of liver, kidney, small intestine, large intestine, and lung in any of the species studied. We are currently completing PCR analysis of the tissues listed above as well as nasal turbinates. Initial results suggest low likelihood of persistence of ONRAB® in the environment or in individual animals that contact the vaccine. Our preliminary conclusions suggest that non-target species will not be negatively impacted by the distribution of ONRAB® as part of ORV programs in the United States.